Recent Developments in Wild Rice Conservation, Research, and Use - Banaticla-Hilario, Maria Celeste N.; Sajise, Andres Godwin (Springer, 2022)
In this chapter, we assess the current status of wild Oryza gene bank collections and in situ protection sites. We have identified O. neocaledonica and O. schlechteri as priority species, and Africa and South America as priority regions for ex situ and in situ conservation. We review recent genetic diversity studies and explained how information on population genetic structure, ecogeographic differentiation within species, and intra- and interspecific gene flow can be used in enhancing the effectivity and efficiency of conservation methods. We emphasize the need for further studies on species-specific dormancy-breaking treatments and on seed longevity of wild rice species under storage conditions. We discuss the potentials of molecular taxonomic markers, tissue culture, and plant-dwelling symbionts in improving gene bank practices. Finally, we present the significant contributions of wild Oryza species to rice improvement.